Non-formal spaces of socio-cultural accompaniment: Responding to young unaccompanied refugees – reflections from the Partispace project - Batsleer, Janet; Andersson, Björn; Liljeholm Hansson, Susanne; Lütgens, Jessica; Mengilli, Yağmur; Pais, Alexandre; Pohl, Axel; Wissö, Therése (European educational research journal EERJ, 2018)
Drawing on research in progress in the Partispace project we make a case for the recognition of the importance of non-formal spaces in response to young refugees across three different national contexts: Frankfurt in Germany; Gothenburg in Sweden; and Manchester in the UK. It is argued that recognition of local regulation and national controls of immigration which support climates of hostility makes it important to recognise and affirm the significance of non-formal spaces and ‘small spaces close to home’ which are often developed in the ‘third space’ of civil society and arise from the impulses driven by the solidarity of volunteers. In these contexts it is important that practices of hospitality can develop which symbolically reconstitute refugees as hosts and subjects of a democratic conversation, without which there is no possible administrative solution to the refugee crisis. It is essential that educational spaces such as schools, colleges and universities forge strong bonds with such emergent spaces.